Efektifitas Terapi Musik Klasik pada Ibu Hamil dengan Kecemasan - Irmasanti Fajrin; Dian Pratiwi; Rouvie Maramis (Window of Nursing Journal, 2026)
Anxiety in pregnant women is a psychological condition that can lead to physiological impacts such as increased blood pressure, early uterine contractions, sleep disturbances, and the risk of premature labor. In 2024 at the Tandengan Public Health Center, out of 103 pregnant women, 21 (27.63%) experienced anxiety. This study aims to determine the effectiveness of classical music therapy in reducing anxiety levels among pregnant women.The research design is a quasi-experiment with a one-group pretest-posttest approach. The population consisted of 43 pregnant women, and the sample size was determined using the Slovin formula at a 10% error margin, resulting in 30 respondents. The intervention was conducted for 3 consecutive days, twice a day (morning at 10:00 AM and evening at 9:00 PM), for 10–15 minutes each session using Mozart's classical music via headsets.The Standard Operating Procedure (SOP) for the intervention included: preparation of equipment and music playlists, informed consent, ensuring a comfortable position, maintaining privacy, fitting the headset, adjusting the volume, administering the music, and post-therapy evaluation. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS) questionnaire.The Wilcoxon test results showed a significant decrease in anxiety (p = 0,000). Classical music therapy is effective in reducing anxiety in pregnant women and can serve as a simple, safe, and affordable non-pharmacological intervention. It is recommended that this therapy be integrated into antenatal care programs to help pregnant women achieve mental readiness before childbirth.